2002
DOI: 10.1023/a:1020920820767
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Obesity is a heterogeneous condition of variable aetiology, generally associated with pathologies such as arterial hypertension, hyperlipidaemia, diabetes and cardiac disease. These conditions, either themselves or because of the various treatments used, may further modify blood rheology in an arbitrary manner. Therefore, analyses of changes in the blood rheology induced by obesity in humans have had differing and controversial results. In our laboratory, a model of hypertriglyceridaemic obesity is provided by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…These changes in blood cell number could potentially result in raised blood viscosity, although this remains to be determined here. Previous studies have shown that high-fat feeding in animals can significantly increase the number of WBC in specific lymphocyte subtypes and enhance blood viscosity [ 25 27 ]. As elevated haematocrit is associated with worse outcome in stroke patients [ 28 , 29 ] and after experimental stroke in mice [ 30 ], these changes in blood cell number after high-fat feeding might contribute to worse outcome in obese mice.…”
Section: Discussionmentioning
confidence: 99%
“…These changes in blood cell number could potentially result in raised blood viscosity, although this remains to be determined here. Previous studies have shown that high-fat feeding in animals can significantly increase the number of WBC in specific lymphocyte subtypes and enhance blood viscosity [ 25 27 ]. As elevated haematocrit is associated with worse outcome in stroke patients [ 28 , 29 ] and after experimental stroke in mice [ 30 ], these changes in blood cell number after high-fat feeding might contribute to worse outcome in obese mice.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, RBC aggregability, which is induced by fibrinogen, is well documented [39]. Similarly, blood and plasma viscosity are influenced by the concentration of lipid fractions, such as total CHO, LDL, or the triglyceride [13, 40, 41, 42, 43]. It was also shown that high-density lipoprotein (HDL) has an inverse correlation to RBC deformability [13].…”
Section: Discussionmentioning
confidence: 99%